Experimental Evaluation of Using Gamification in Software Engineering Education in Software Requirements - Sergio Galvan-Cruz; Mirna Muñoz; Jezreel Mejía; Adriana Peña; David Bonilla-Carranza (CLEI Electronic Journal)
Education in Software Engineering traditionally focuses on techniques used in the classroom that generate stress and disinterest in the topics taught; therefore, a significant challenge to the use of more effective and motivating teaching methods to achieve student learning. Moreover, the lack of motivating teaching methods results in a lack of perception regarding the importance of artifacts that come together with software, such as documentation. Consequently, students prefer to focus only on development without paying attention to the necessary artifacts, so the maintenance and update of software in later stages are negatively affected. In response to this problem, the need arises to incorporate more dynamic and effective teaching approaches that encourage student participation and commitment. In this sense, Gamification is presented as an innovative solution that has gained increasing interest in Software Engineering and other fields of education. This research aims to provide the results of a case study in which Gamification has been used in teaching Software Engineering for the topic of software requirements within a master's software engineering course.